Iron stores assessment in alcoholic liver disease. (June 2013) - Costa Matos, Luís; Batista, Paulo; Monteiro, Nuno; Ribeiro, João; Cipriano, Maria A.; Henriques, Pedro; Girão, Fernando; Carvalho, Armando
Abstract Background: The relation between alcoholic liver disease (ALD) and iron overload is well known. Liver biopsy is the gold standard for assessing iron stores. MRI is also validated for liver iron concentration (LIC) assessment. We aimed to assess the effect of active drinking in liver iron stores and the practicability of measuring LIC by MRI in ALD patients. Materials and methods: We measured LIC by MRI in 58 ALD patients. We divided patients into two groups – with and without active alcoholism – and we compared several variables between them. We evaluated MRI-LIC, liver iron stores grade, ferritin and necroinflammatory activity grade for significant correlations. Results: Significant necroinflammation (40.0% vs. 4.3%), LIC (40.1 vs. 24.3 µmol/g), and ferritin (1259.7 vs. 568.7 pmol/L) were significantly higher in drinkers. LIC values had a strong association with iron stores grade (rs = 0.706). Ferritin correlated with LIC (rs = 0.615), iron stores grade (rs = 0.546), and necroinflammation (rs = 0.313). The odds ratio for elevated serum ferritin when actively drinking was 7.32. Conclusion: Active alcoholism is associated with increased ALD activity. It is also the key factor in iron overload. Scheuers' semiquantitative score with Perls' staining gives a fairly accurate picture of liver iron overload. Serum ferritin also shows a good correlation with LIC values and biopsy iron stores grade. As most patients present only with mild iron overload, serum ferritin measurement and semiquantitative evaluation of iron stores are adequate, considering MRI high cost. However, if MRI is required to evaluate liver structure, LIC assessment could be performed without added cost.